Engraving of the birth of Louis of France, 'Duke of Burgundy', in 1682 - Auteur inconnu (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Engraving of the birth of Louis of France, "Duke of Burgundy", in 1682.
Droits : Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; patrimoine; wikimedia commons; Iconographie